A concise review of dental sealants in caries management - Toby Cheuk-Hang Ng; Chun-Hung Chu; Ollie Yiru Yu (Frontiers Media S.A., 2023)
This concise review provides an update of the use of dental sealants. Dental sealants protect a tooth from caries development by providing a physical barrier to microorganism colonisation and creating a favorable environment for patients to clean. Some sealants release fluoride ions to promote remineralization. Dental sealants can be applied on pits and fissures of primary and permanent teeth to prevent and arrest early enamel caries. They are effective in caries prevention. The preventive fraction of resin sealant is up to 61% after 5 years. Dental sealants can be classified as resin, glass ionomer and hybrid (compomer or giomer) according to the material. Recent studies from 2012 to 2022 showed resin sealant has a high retention rate of up to 80% after 2 years, whereas glass ionomer sealants is 44%. Chemical etching with 37% phosphoric acid is the standard of care, whereas laser or air-abrasion cannot does not increase the sealant retention rate. Moist control is critical and studies found the use of rubber dam and cotton rolls had similar success for sealant retention. The longevity of dental sealant is also associated with clinical operative factors, including approaches of moisture control, enamel pretreatment, selection of dental adhesive, and time of acid etching.